2019
DOI: 10.2147/sar.s164261
|View full text |Cite
|
Sign up to set email alerts
|

<p>Current perspectives on the impact of Kratom use</p>

Abstract: The leaves from the tree Mitragyna speciosa, commonly known as Kratom, in the coffee plant family (Rubiaceae) are commonly used in their native habitat of Southeast Asia as a stimulant to sustain energy during hard day labor and as an opioid-like analgesic and sedative. Traditional and modern uses overlap based on the effects of the leaf extract which has also gained popularity in the United States and Europe in the last two decades. Kratom has and is being used for the mitigation of opioid withdrawal symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
116
3
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(124 citation statements)
references
References 40 publications
(80 reference statements)
2
116
3
3
Order By: Relevance
“…Based on these latter effects, Malaysian authorities deemed kratom to have addiction potential, prohibiting kratom use in that country (Khalil et al, 2020). The legal status of kratom varies in other countries depending on region, and in the US, by state, city, and county (Veltri and Grundmann, 2019). Accordingly, sales in the US and several European countries continue to flourish (Henningfield et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Based on these latter effects, Malaysian authorities deemed kratom to have addiction potential, prohibiting kratom use in that country (Khalil et al, 2020). The legal status of kratom varies in other countries depending on region, and in the US, by state, city, and county (Veltri and Grundmann, 2019). Accordingly, sales in the US and several European countries continue to flourish (Henningfield et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…4 Kratom can also cause dependence and addiction, which was highlighted in a recent review co-authored by Dr. Grundmann. 5 It is our opinion that the current evidence regarding the side effects and potential for adverse consequences associated with kratom use are sufficient to conclude that it should not remain available as an herbal supplement.…”
mentioning
confidence: 98%
“…Studies have found that 7-hydroxymitragynine is the main contributor to the plant’s toxicity and the development of addiction symptoms. In 2014, Singh et al [ 51 ] reported a cross-sectional survey investigating the correlation between frequency and quantity of kratom consumption, and the risk of addiction development and the severity of withdrawal symptoms and craving in regular user [ 216 ]. Cessation of kratom use produced physical withdrawal symptoms similar to those of opiate addiction including pain, sleep disorders, muscle spasms, watery eyes, runny nose, hot flashes, fever, decreased appetite, diarrhea, and craving.…”
Section: Discussionmentioning
confidence: 99%